Factors Influencing Health Promotion Behaviors of Thai Police Officers - Wattanakitkrileart, Doungrut; Saneha, Chongjit; Panitrat, Rungnapa; Suvarnarong, Klinchaba; Suebsuk, Pannipa; Kedcham, Det (Nursing Science Journal of Thailand, 2011)
Purpose: This study aimed to examine health promotionbehaviors and factors influencing health promotion behaviors ofThai police officer. Design: A correlational predictive study design. Methods: Participants comprised 82 police officers in twometropolitan police stations, Bangkoknoi District, Bangkok,Thailand. The research instruments included a demographic andhealth status questionnaire, health promotion behaviorsquestionnaire, perceived self-efficacy, perceived benefits andbarriers to perform health promotion behaviors questionnaires.The data were analyzed using descriptive statistics and multipleregression. Main findings: The participants’ age ranged from 23-58 years old.Perceived self-efficacy and perceived benefits to perform healthpromotion behaviors were positively and significantly correlatedwith health promotion behaviors (r = .695 and r = .514, p < .01,respectively). Perceived barriers to perform health promotionbehaviors had a significant negative relationship with healthpromotion behaviors (r = - .349, p < .01). Only perceived selfefficacyto perform health promotion behaviors significantlypredicted health promotion behaviors (p < .01). The three factorscould explain 50.8% of the variance in health promotionbehaviors (p < .05). Conclusion and recommendations: The results demonstratedthat perceived self efficacy was a significant predictor of healthbehaviors. Nurses should therefore develop nursing interventionsto enhance awareness and self efficacy among police officers toperform health promotion behaviors.